DETERMINACIÓN DE RIESGOS Y SEÑALIZACIÓN EN LA EMPRESA BIOALIMENTAR COMPANÍA LIMITADA - Guerrero Merino, Irma Maribel (2010)
Currently one of the bigger concerns of companies the implementation of industrial safety which accepts not only to meet existing needs in regard to the physical integrity of its employees but also to prevent their resources. Inside this context is Bioalimentar Company CIA LTDA. That is continuously looking for to improve through the evaluation and control of its staff and products. The company doesn’t have a department of industrial safety that the work began with the identification of jobs and their activities. Subsequently was to identified the different risks in the company. For the evaluation of the risks encountered using William Fine the method, method dose mediator and NFPA method